2012
DOI: 10.1118/1.4735221
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐163: Thin‐Film Organic Photocell (OPV) Properties in MV and KV Beams for Dosimetry Applications

Abstract: With proper calibration, the OPV cells could be used for online radiation dose measurement for quality assurance and patient safety purposes. Their response to kV beam show promising potential in development of low cost kV radiation detection devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kingsley et al 4 used OPVs exposed to 6 MV clinical beams and found that these devices have sensitivities of an order of magnitude greater than a commercial silicon detector. Separately, Ng et al 5 investigated the dosimetric properties of thin film OPV cells for various irradiation conditions in medical applications of x-rays. The response of these cells was determined for different thicknesses and sizes and was found to be linear with dose and cell size, and slightly decreasing with the thickness of the active layer.…”
Section: Introductionmentioning
confidence: 99%
“…Kingsley et al 4 used OPVs exposed to 6 MV clinical beams and found that these devices have sensitivities of an order of magnitude greater than a commercial silicon detector. Separately, Ng et al 5 investigated the dosimetric properties of thin film OPV cells for various irradiation conditions in medical applications of x-rays. The response of these cells was determined for different thicknesses and sizes and was found to be linear with dose and cell size, and slightly decreasing with the thickness of the active layer.…”
Section: Introductionmentioning
confidence: 99%